Utilization of Natural Products as a Source of Novel Antibiotics: A Literature Review - Nur Afni (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
Antibiotic resistance is a growing global health concern that threatens the effectiveness of current treatments against bacterial infections. Natural products have long served as essential reservoirs for the discovery of bioactive compounds, including antibiotics, owing to their structural diversity and ecological functions. This literature review highlights recent advances (2016–2025) in the identification and development of novel antibacterial compounds derived from natural sources such as medicinal plants, soil actinomycetes, marine organisms, endophytes, and extremophiles. It also discusses the molecular mechanisms underlying their antibacterial actions and addresses modern approaches in natural product-based drug discovery, including genome mining, metabolomics, artificial intelligence, and synthetic biology. Despite various challenges, such as the rediscovery of known molecules and low yields, innovative strategies continue to drive the development of promising antibiotic candidates. This review emphasizes the untapped potential of natural resources and advanced technologies in tackling the global antimicrobial resistance crisis.